Nepal and Bangladesh - Transport and HIV Portfolio Review and Situation Analysis - World Bank (World Bank, 2012)
This review report focuses on the HIV component of the World Bank Bangladesh and Nepal transport infrastructure projects as at the end of 2009. This report is prepared with the following three objectives: 1) knowledge improved and lessons learned from HIV and AIDS activities developed within the road projects financed by the World Bank in Bangladesh and Nepal as of the end of 2009; 2) knowledge base built on current HIV and AIDS programs in the transport sector in Bangladesh and Nepal to serve as a reference for future World Bank projects in the transport sector in South Asia; 3) guidance provided to the draft regional strategy for HIV prevention in the transport sector of the Bank's South Asia region. The World Bank has a comparative advantage in promoting the inclusion of a transport sector response within the new national AIDS strategies being formulated for Bangladesh in 2010 and Nepal in 2011. The Bank may consider making the model HIV clause in the transport projects mandatory, consistent with other funders, such as the Asian Development Bank (ADB), to improve aid effectiveness.